2018
DOI: 10.1002/brb3.1088
|View full text |Cite
|
Sign up to set email alerts
|

New vessels formation in young strokes with isolated steno‐occlusive MCA

Abstract: ObjectiveNew vessels formation (NVF) along the steno‐occlusive middle cerebral artery (MCA) is often observed in digital subtraction angiography (DSA) imaging. In the study, we aim to explore the clinical relevance of NVF in young ischemic stroke patients with isolated middle cerebral artery (MCA) stenosis.MethodsWe retrospectively reviewed the digital subtraction angiography (DSA) images of 93 young ischemic stroke patients (age ≤ 45 years old) in our center from January 2006 to June 2016. All the patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, the differences of clinical significance between them are still unclear. 19,20 In this study, therefore, the hemispheres with stenosis in the terminal portion of the internal carotid artery and the proximal portions of the MCA and ACA were strictly judged as moyamoya disease, and hemispheres without the stenosis in the terminal portion of the internal carotid artery were temporarily named as questionable (Q) manifestations ( Figure 1 ). As a result, all patients were classified into 4 categories: the patients with bilateral moyamoya hemispheres, those with unilateral moyamoya hemisphere, those with moyamoya hemisphere plus “Q” hemisphere, and those with bilateral or unilateral “Q” hemisphere.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the differences of clinical significance between them are still unclear. 19,20 In this study, therefore, the hemispheres with stenosis in the terminal portion of the internal carotid artery and the proximal portions of the MCA and ACA were strictly judged as moyamoya disease, and hemispheres without the stenosis in the terminal portion of the internal carotid artery were temporarily named as questionable (Q) manifestations ( Figure 1 ). As a result, all patients were classified into 4 categories: the patients with bilateral moyamoya hemispheres, those with unilateral moyamoya hemisphere, those with moyamoya hemisphere plus “Q” hemisphere, and those with bilateral or unilateral “Q” hemisphere.…”
Section: Methodsmentioning
confidence: 93%
“…They may be almost identical to the cases that have previously been reported under the terms such as isolated MCA stenosis. 19,20 Their pathogenesis has long been unknown, but recent studies have revealed a high frequency of heterozygotes at RNF213 gene, a susceptibility gene for moyamoya disease, in such cases. Some cases are also reported in which isolated MCA stenosis progressed to typical moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported on isolated MCA disease with or without NVF. 7 , 8 The diagnostic points of the disease include unilateral MCA disease (stenosis over 50% or occlusion); no other intracranial steno-occlusive lesion; patients younger than 55 years; no atherosclerotic risk factor; and exclusion of vasculitis, dissection, and emboligenic sources. Isolated MCA disease with NVF is similar to T-MCA, and T-MCA may be defined as a variety of isolated MCA disease with NVF.…”
Section: Discussionmentioning
confidence: 99%
“… 5 The most important differential diagnosis is moyamoya disease (MMD), but differentiation is no longer difficult according to the current diagnostic criteria of MMD. 6 On the other hand, recent studies have reported isolated MCA disease with or without new vessel formation (NVF) 7 , 8 and have indicated that with NVF, the disease is similar to T-MCA.…”
mentioning
confidence: 99%